Dimethyl fumarate modulates the Treg–Th17 cell axis in patients with psoriasis. (26th July 2020) - Sulaimani, J.; Cluxton, D.; Clowry, J.; Petrasca, A.; Molloy, O.E.; Moran, B.; Sweeney, C.M.; Malara, A.; McNicholas, N.; McGuigan, C.; Kirby, B.; Fletcher, J.M.
Summary: Background: Dimethyl fumarate (DMF) is the active ingredient of Skilarence™ and Tecfidera™, which are used for the treatment of psoriasis and multiple sclerosis, respectively. Various immunomodulatory mechanisms of action have been identified for DMF; however, it is still unclear what effects DMF exerts in vivo in patients with psoriasis. Objectives: In this study we examined the effects of DMF, both in vivo and in vitro, on T cells, which play a key role in the pathogenesis of psoriasis. Methods: The frequency of T‐cell subsets was examined by flow cytometry in untreated patients with psoriasis or those treated with DMF. The effects of DMF in vitro on T‐cell survival, activation and proliferation, and cell‐surface thiols were assessed by flow cytometry. Results: In patients with psoriasis treated with DMF we observed an increase in the frequency of T regulatory (Treg) cells and a decrease in T helper (Th)17 lineage cells and the associated cytokines interleukin‐17, interleukin‐22 and granulocyte–macrophage colony‐stimulating factor. T cells cultured in vitro with DMF exhibited reduced viability, and inhibition of activation and proliferation in response to stimulation due to the oxidative effects of DMF. However, the frequency of Treg cells increased in the presence of DMF due to their heightened ability to resist DMF‐induced oxidative stress. Conclusions: DMF enhanced the ratio of Treg cells to Th17 cells in patients with psoriasis, in patients with multiple sclerosis and in vitro . Furthermore, our data suggest that this is at least in part as a result of the differential effects of DMF on Treg cells compared with conventional T cells. Abstract : What is already known about this topic? Dimethyl fumarate is an effective treatment for psoriasis and multiple sclerosis. T cells play a key role in the pathogenesis of psoriasis, and the Treg–Th17 cell axis is dysregulated. Multiple mechanisms of action have been described for DMF; however, its effects on T cells in patients with psoriasis have not been elucidated. What does this study add? The Treg to Th17 ratio was enhanced in patients with psoriasis treated with DMF. DMF also increased the ratio of Treg cells to Th17 cells in vitro, by increasing the frequency of Treg cells. Treg cells exhibited an increased ability to resist the oxidative stress induced by DMF in vitro ; this is a new mechanism of action for DMF. What is the translational message? The Treg–Th17 axis is known to be dysregulated in psoriasis, and this study indicates that DMF can modulate this axis in favour of regulation. The ability of Treg cells to resist the oxidative stress induced by DMF is likely to contribute to its mechanism of action. The selective reduction of Th17 cells without a reduction in Th1 cells or Treg cells explains the efficacy of DMF in psoriasis. Linked Comment:  Mostafa et al. Br J Dermatol 2021; 184:389–390 . Plain language summary available online